Relationship-Building Skills of Child-Rearing Mothers in Japanese Communities - Hikaru Honda; Nobuko Matsuda; Michiyo Hirano; Kazuko Saeki (Nursing Research and Practice)
This study elucidated the skills of mothers who used to build positive interpersonal relationships with people they met through child-rearing. The research method was qualitative descriptive study. The participants were 24 mothers who had children between ages of one and four years. These participants were recruited at child-rearing salons and childcare centers located in various municipalities in Japan. The survey period was from September 2013 to July 2014. The mothers’ interpersonal relationship-building skills were described by six categories: “ability to strive for new encounters,” “ability to try to interact socially with others,” “ability to choose compatible people,” “ability to continuously maintain good relationships,” “ability to take action suitable to a situation,” and “ability to build positive relationships with parents-in-law.” Cognitive aspects of assessing and understanding the interactions that occur during exchanges and behavioral aspects guided by these cognitions were identified within these skills. This study contributed to providing a framework to understand mothers’ interpersonal relationship-building skills for public health nurses involved in child-rearing support.